Employment, hours and optimal monetary policy - Maarten Dossche; Vivien Lewis; Céline Poilly (Deutsche Bundesbank, 2015)
We characterize optimal monetary policy in a New Keynesian search-and-matching model where multiple-worker firms satisfy demand in the short run by adjusting hours per worker. Imperfect product market competition and search frictions reduce steady state hours per worker below the efficient level. Bargaining results in a convex 'wage curve' linking wages to hours. Since the steady-state real marginal wage is low, wages respond little to hours. As a result, firms overuse the hours margin at the expense of hiring, which makes hours too volatile. The Ramsey planner uses inflation as a instrument to dampen inefficient hours fluctuations.
Keywords: E30; E50; E60; 330; employment; hours; wage curve; optimal monetary policy